Communication in Chronic Disease Care: A Collaborative Conversation Map - Sanjay Kalra; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Chronic diseases require long term commitment from both the patient and the treating physician for improving their clinical outcomes. This journey can be made more easier if a proper communication bridge can be made between both of them. This paper describes an alliterative C-based flow-chart to describe a Collaborative Conversation Map for chronic disease care. It crafts a map which serves as a checklist for chronic health care providers, especially those dealing with obesity and diabetes. This conversation map is concordant with the WATER (welcome warmly, ask and assess, tell truthfully, explain with empathy, reassure and return) conversation approach described earlier. Keywords: Chronic disease, diabetes, obesity, person centred care, psychosocial issues, therapeutic patient education